Strategic orientations, the mediating effect of absorptive capacity and innovation: a study among Malaysian manufacturing SMEs - Al Mamun, Abdullah; Fazal, Syed Ali; Mohiuddin, Muhammad; Su, Zhan (World Scientific Publishing Europe Ltd., 2019)
Strategic orientations (SOs) and absorptive capacity can significantly enhance innovation capacity in manufacturing Small and Medium Enterprises (SMEs). This study explores the relationship of SOs i.e., Market Orientations (MOs), Entrepreneurial Orientations (EOs) and Customer Orientations (COs) to absorptive capacity on the one hand, and to innovation on the other hand. The study also delves into the issue of how absorptive capacity mediates the effects of SOs on innovation in manufacturing SMEs from emerging countries’ perspective. This study uses a cross-sectional design and quantitative data collected through a structured interview of top managers from 360 manufacturing SMEs. The findings show that MO, EO and CO have positive and significant effects on innovation and that absorptive capacity partially mediates SOs’ effects on innovation.